Mentalization and empathy as predictors of violence in schizophrenic patients: Comparison with nonviolent schizophrenic patients, violent controls and nonviolent controls. (October 2018) - Kristof, Zsuliet; Kresznerits, Szilvia; Olah, Mate; Gyollai, Agoston; Lukacs-Miszler, Katalin; Halmai, Tamas; Fountoulakis, Konstantinos N.; Tenyi, Tamas; Dome, Peter; Gonda, Xenia
Highlights: There are no differences in mentalisation in violent and nonviolent schizophrenics. Worse mentaliation is related to schizophrenia but not violence in this illness. Violence in schizophrenics and controls has different predictors. Abstract: There are conflicting results concerning risk of violence in schizophrenia. Empathy and mentalization deficits are associated both with schizophrenia and violence, however, there are only a few studies with equivocal results concerning their relationship. 88 violent and nonviolent paranoid schizophrenic and violent and nonviolent control males in psychiatric, forensic psychiatric and correctional institutions completed the Ekman 60 Faces test, Faux Pas Recognition Test, Eysenck IVE test, Interpersonal Reactivity Index, and the Spielberger Anger Expression Scale. Data were analysed with ANOVA and logistic regression models. Significant group differences with a characteristic pattern were detected in mentalization, facial affect recognition, fear and anger recognition, interpersonal distress, and frequency of direction of anger expression. Predictors of violent behaviour were different in the schizophrenic and non-schizophrenic groups. Lack of major differences in empathy and mentalization between violent and nonviolent schizophrenia patients suggests that such deficits are core features of schizophrenia but do not determine emerging violence in this illness. Our results emphasise the importance of distinguishing between violence related to core positive symptoms of schizophrenia and that emerging from independent comorbid antisocial personality traits in order to identify targets for screening, detection, prevention and management of violence risk in different subpopulations of schizophrenia patients.